Design of a microstrip dual-frequency diplexer using microstrip cells analysis and coupled lines components. Issue 7 (15th February 2017) - Noori, Leila; Rezaei, Abbas
Abstract : In this paper, a microstrip diplexer composed of two similar resonators is designed. The proposed resonator is consisting of four microstrip cells, which are connected to a coupled lines structure. In order to select a suitable geometric structure, first, all cells are assumed as undefined structures where there is a lack of basic information about their geometry and dimensions. Then, an equivalent LC circuit of the coupled lines is introduced and analyzed to estimate the general structure of the resonator respect to a requested resonance frequency. The proposed diplexer is designed to operate at 2.36 and 4 GHz for wireless applications. The insertion losses (S21 and S31 ) are decreased significantly at the resonance frequencies, so that they are 0.2 and 0.4 dB at 2.36 and 4 GHz, respectively. The designed diplexer is fabricated and measured and the measurement results are in a good agreement with the simulations.